AB1342 Rheumatic diseases prevalence and quality of life in saraguro indigenous populations of ecuador: a cross-sectional community-based study. (12th June 2018) - Guevara-Pacheco, S.; Feican-Alvarado, A.; Valdiviezo-Vicuña, W.; Molina-Alvarado, G.; Ortega-Mendoza, N.; Delgado-Pauta, J.; Montaleza-Neira, M.; Chimbo-Pullaguari, L.; Hernandez, M.; Cervera-Segura, R.; Sanin, L.H.; Pelaez-Ballestas, I.; et al.
Abstract : Background: Rheumatic diseases are more prevalent and aggressive in indigenous population groups, in which providing medical attention poses a challenge for the rheumatologist. Objectives: To estimate the prevalence of musculoskeletal (MSK) disorders and rheumatic diseases in the Saraguro indigenous people and their impact on the quality of life. Methods: Cross-sectional analytical study carried out in the community of Saraguro using the COPCORD methodology. Mixed and randomised sampling techniques were employed. The following validated questionnaires were administered: 1. Screening for musculoskeletal (MSK) disorders and rheumatic diseases. 2. A sociodemographic questionnaire. 3. A functional capacity questionnaire (HAQ-DI) and an instrument to measure workload and repetitive movements. 4. Quality of life (EQ-5D3L). Cases with MSK disorders were reviewed by rheumatologists within the community. Results: A total of 2687 individuals over 18 years of age participated, with an average age of 44 (SD 19.9) years; 1690 (62.9%) were women, 872 (32.4%) were Kwichua speakers; 2108 (78.4%) were employed, of these 32.5% were farm workers. MSK pain was reported in 1244 (46.3%); pain was severe in 448 (36%); 868 (69.7%) used some medical treatment and 1013 (81.4%) used traditional medicine. The most prevalent self-reported comorbidities were anxiety (55.5%) and depression (46.8%). Rheumatic diseases were diagnosed in 861/1244 (69.2%), with the following most prevalent conditions: Low back pain 9.3%, hand osteoarthritis 7.2%, knee osteoarthritis 6.5%, RRPS (rheumatic regional pain syndrome) 5.8%, fibromyalgia 1.8%, rheumatoid arthritis (RA) 1.3%. Disability (HAQ >0.8) was observed in 356 (28.6%), whereas loading and pushing objects heavier than 20 kg and shaking hands was significantly associated with MSK pain. The regression models showed a significant association with a lower quality of life in those with lower education levels (OR=0.89; 95% CI 0.88 to 0.91, p<0.001), physically demanding jobs (OR=0.54; 95% CI 0.42 to 0.69, p<0.001), cooking with firewood (OR=1.55; 95% CI 1.05 to 2.30, p=0.02), high blood pressure (OR=2.31; 95% CI 1.73 to 3.10, p<0.001), and rheumatic diseases, especially RA (OR=5.52; 95% CI 2.48 to 12.27, p<0.001) and hands OA (OR=2.05; 95% CI 1.44 to 2.91, p<0.001). One finding is that having RA was associated with cooking with firewood, and that smoking was almost nonexistent in this population. This suggests that wood smoke pollutants play a similar role to that described with tobacco smoke. Conclusions: A high prevalence of MSK disorders, rheumatic diseases and RA was found. The prevalence of rheumatic diseases was associated with a lower education level, cooking with firewood, and physically demanding jobs. The greatest impact on the quality of life in all dimensions was on the individuals with RA and hand OA. Acknowledgements: Funding: Research Dept. Universidad de Cuenca, Ecuador Disclosure of Interest: None declared